Effect of shoulder and hand position on sport-specific grip force in rock climbers - Nelson-Wong, E.; Crawley, J.; Cowell, K.; Parker, L.; Higgins, E.; Huang, S.; Lorbiecki, C.; Wood, S. (The Sport Journal, 2023)
Purpose Rock climbing has become popular as a recreational activity. Overuse injuries of fingers and hands are common due to uniquely high demands placed on these structures. Climbers adapt hand positions to match types of holds on rock climbing routes, with open-hand and half-crimp positions being most used. The primary purpose of this study was to explore differences in climbing-specific grip strength between 2 hand positions and 2 shoulder positions.